Electrostatic Assembly Guided Synthesis of Highly Luminescent Carbon‐Nanodots@BaSO4 Hybrid Phosphors with Improved Stability. Issue 6 (5th December 2016) - Zhou, Ding; Zhai, Yuechen; Qu, Songnan; Li, Di; Jing, Pengtao; Ji, Wenyu; Shen, Dezhen; Rogach, Andrey L.
Abstract : Carbon nanodots (CNDs)@BaSO4 hybrid phosphors are fabricated in an easy and low‐cost process by sequentially assembling Ba 2+ and SO4 2− ions onto the surface of carbon nanodots through electrostatic attraction. CNDs act as the nucleus to attract these reactive ions and provide the luminescent centers in the hybrid phosphors. This strategy is versatile for a variety of negatively charged CNDs with different emission colors. The advantage of the resultant hybrid phosphors is that their luminescence exhibits excellent thermal and photostability, as well as remarkable resistance to strong acid/alkali and common organic solvents. These merits allow for the fabrication of CNDs‐based light‐emitting diodes using the CNDs@BaSO4 hybrid phosphors as a color conversion layer. Abstract : Carbon‐nanodots@BaSO4 hybrid phosphors are fabricated via electrostatic assembly guided process . Owing to their excellent stability and strong photoluminescence, hybrid phosphors have a great potential for carbon nanodots‐based white light‐emitting diodes.